2022
DOI: 10.1007/s10802-022-00990-6
|View full text |Cite
|
Sign up to set email alerts
|

Construct Validation for Toddler-Solicited Maternal Comforting Behavior as Relevant to Family Accommodation and Child Anxiety Risk

Abstract: Reciprocal parent-child interactions are theorized to play a crucial role in child anxiety development and maintenance. The current study tested whether toddler-solicited maternal comforting behavior in low-threat (mildly challenging and novel) situations may be a unique, early indicator of anxiety-relevant interactions. Controlling for other types of maternal comforting behavior, a path model tested solicited comforting behavior in a low-threat context in relation to both family accommodation (FA) and child a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“… 30 In recent years, researchers have discovered significant positive correlations between restricted and repetitive behaviors and interests and overall family accommodation behaviors and their sub scores in children with autism spectrum disorder. 31 Research has also shown that family accommodation and child anxiety are bidirectionally related between the age 4 years and school age, 32 and youths with anxiety disorders report greater family accommodation than control groups. 33 In addition, family accommodation of restricted and repetitive behaviors occurs frequently and is linked to greater symptom severity in families of children with autism 34 and family accommodation can have a significant impact on the child’s anxiety.…”
Section: Introductionmentioning
confidence: 99%
“… 30 In recent years, researchers have discovered significant positive correlations between restricted and repetitive behaviors and interests and overall family accommodation behaviors and their sub scores in children with autism spectrum disorder. 31 Research has also shown that family accommodation and child anxiety are bidirectionally related between the age 4 years and school age, 32 and youths with anxiety disorders report greater family accommodation than control groups. 33 In addition, family accommodation of restricted and repetitive behaviors occurs frequently and is linked to greater symptom severity in families of children with autism 34 and family accommodation can have a significant impact on the child’s anxiety.…”
Section: Introductionmentioning
confidence: 99%